The distribution of the bivalve mya arenaria l. on the romanian shore of the Black Sea - Petran, Adriana; Gomoiu, Marian Traian (Cercetări Marine - Recherches Marines, 2026)
On the basis of 590 samples collected during 1970 and 1971 from the superior infralittoral strip - to the depth of 10m, in a network of 105 stations, the qualitative and quantitative spreading of the bivalve Mya arenarla L. on the Romanian shore is established, the species having recently penetrated into the Black Sea. The registered densities and biomasses show that, during the last 4-5 years, Mya settled perfectly off the Romanian shore in fine sediment zones (sand, muddy sand and sandy mud), in some places reaching values of over 8,000specimens/m2 and 16,000g/m2. It has been noticed, on the basis of obtained data, that the setting of Mya off the Bomanlan shore is still a developing process.